2003
DOI: 10.1074/jbc.m306398200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of cAMP-induced Allosteric Changes in Mutants T127I, S128A, and T127I/S128A of the cAMP Receptor Protein from Escherichia coli

Abstract: The cAMP receptor protein (CRP) regulates the expression of several genes in Escherichia coli. The protein is a homodimer, and each monomer is folded into two distinct structural domains. After allosteric transitions resulting from the binding of cAMP, CRP specifically binds to DNA and activates transcription. We have used stopped-flow fluorometry measurements of CRP mutants bearing amino acid substitutions T127I, S128A, and T127I/S128A to study the kinetics of conformational changes in the protein induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Thus, the data are consistent with our previous kinetic studies using wt CRP [21], CRP T127I and CRP S128A mutants [22], suggesting that the observed change in the fluorescence intensity of labeled proteins resulted from a conformational change of the double ligated protein. Therefore, the obtained data in the present study were also analyzed in terms of a sequential (KNF) model of allostery, represented by Scheme 2, where K 1 and K 2 are intrinsic dissociation constants for the binding of the first and the second molecule, respectively; k c and k −c are the rate constants describing the conformational change, CRP and CRP' represent the protein before and after that process, respectively.…”
Section: Extrinsic Fluorescence Measurementsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, the data are consistent with our previous kinetic studies using wt CRP [21], CRP T127I and CRP S128A mutants [22], suggesting that the observed change in the fluorescence intensity of labeled proteins resulted from a conformational change of the double ligated protein. Therefore, the obtained data in the present study were also analyzed in terms of a sequential (KNF) model of allostery, represented by Scheme 2, where K 1 and K 2 are intrinsic dissociation constants for the binding of the first and the second molecule, respectively; k c and k −c are the rate constants describing the conformational change, CRP and CRP' represent the protein before and after that process, respectively.…”
Section: Extrinsic Fluorescence Measurementsupporting
confidence: 91%
“…Because the estimated value for the wt CRP is low and equals to 0.032, one can expect that almost all double ligated wt CRP would exist in the active conformation [21]. Similarly to the mutation introduced at positions 127 and 128 [22], the amino acid substitution at position 138 can also shift the equilibrium between the two conformational forms of CRP towards the low or high activity conformation ( Table 3). The affinity can be characterized by the dissociation constants of the considered mutants from the promoter region, which was determined for the lac operon promoter.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As a consequence, there is a significant reduction in the affinity of the binding sites localized between the protein domains, and the dissociation constant for these sites is about 8.5 m M . The parameters of cyclic AMP binding to both binding sites determined by kinetic experiments unambiguously show that the point mutation perturbs the communication between the protein domains [Polit et al, 2003b].…”
Section: Cyclic Amp Binding By Crpmentioning
confidence: 99%